Evaluación in vitro del potencial osteogénico de las células madre Mesenquimales de origen dental estimuladas con una matriz de fibrina bioactiva y láser de baja potencia (2021)
Severe bone defects are prevalent in the world. The main aetiology is the trauma associated with motorcycle accidents and violent facts. The prostheses are the conventional treatment. Effective regenerative therapies are currently being developed but are limited by the access, time of therapy, and high cost. More efficient alternatives need to be evaluated.